Understanding the effectiveness of online digital music sampling: an exploratory study. (9th June 2009) - Tu, Yanbin; Lu, Min
Despite the popularity of online digital music and the broad application of digital music sampling, in the existing literature, there is a lack of substantial studies that examine online digital music sampling. This study uses a laboratory experiment to explore the determinants of the five effectiveness dimensions, i.e., evaluation, Willingness-to-Pay (WTP), perceived sampling usefulness, sampling cost and the likelihood of being a free rider, of online digital music sampling. Digital music samples with a higher quality and longer segments were found to increase the sampler's music evaluation and make the evaluation process more useful. Also, the sampler's music evaluation significantly determines his/her WTP. Higher music evaluations not only decrease the sampler's sampling cost during the sampling process, but also reduces the probability that the sampler will take the music sample as a substitute for the original music. This study also shows that the current practice of online digital music sampling is not ideal and music retailers could improve their music sampling strategies by providing digital music samples with longer segments and of higher quality. All of these findings have significant implications for music retailers to use digital music sampling strategies better.